Schauder of (Fixed point) Theories in “Intuitionistic Fuzzy Metric Space” by (Occasionally Weakly Compatible) of Self Mapping - Amani E. Kadhm (Journal of Madenat Alelem University College, 2020)
(schauder) an (IFMS) under using the ideas of four , such that by (OWC) self _mapping, As an application the existence schauder and illustrative by some example of (OWC) an (IFMS) usage one process of theories will be studied using implicit relations. This work may be considered as a general statement of (FMS) and to show another sort from theories in (OWC) which are studied by other researchers and unify many results in the topic for .